Clinicopathological Significance of Leucine-Rich α2-Glycoprotein-1 in Sera of Patients With Pancreatic Cancer. Issue 1 (January 2015) - Furukawa, Kenta; Kawamoto, Koichi; Eguchi, Hidetoshi; Tanemura, Masahiro; Tanida, Tsukasa; Tomimaru, Yoshito; Akita, Hirofumi; Hama, Naoki; Wada, Hiroshi; Kobayashi, Shogo; Nonaka, Yuji; Takamatsu, Shinji; et al.
<x xml:space="preserve">Abstract</x> Objectives Leucine-rich α2-glycoprotein-1 (LRG-1) is an inflammatory protein. Serum LRG-1 levels can reportedly be used as a cancer biomarker for several types of carcinoma. In the present study, we investigated the clinical usefulness of serum LRG-1 levels as a biomarker of pancreatic cancer. Methods A total of 124 patients with pancreatic cancer, 35 patients with chronic pancreatitis (CP), and 144 healthy volunteers were enrolled in the study. Serum LRG-1 levels were assayed by enzyme-linked immunosorbent assay. Immunohistochemistry was used to examine LRG-1 expression in pancreatic cancer tissues. Results Serum LRG-1 levels were significantly increased in patients with pancreatic cancer compared with CP patients and healthy volunteers. The LRG-1 levels increased with progressive clinical stages of pancreatic cancer. Receiver operator curve analysis showed that a combination of carbohydrate antigen 19-9 and LRG-1 resulted in a higher area under the curve for the diagnosis of pancreatic cancer. Positive staining was observed in all cases of pancreatic cancer, but positive signal was scarcely detected in tissues from CP patients or normal surrounding tissue. Conclusions These results suggest that serum LRG-1 is a promising biomarker for pancreatic cancer.